Peranan Budaya Lokal dalam Mendukung Pengembangan Obyek Wisata Walengkabola di Kecamatan Tongkuno Kabupaten Muna - Wa Ode Sitti Hafsah; La Ode Aris (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This article discusses about the role of local culture in supporting the development of tourism object Walengkabola. This article is the the result of field reasearch which was done at Tongkuno District in Muna Regency, Southeast Sulawesi Province. The discussion focuses on identifying local culture which can support the development of tourism object Walengkabola in Tongkuna District Muna Regency, and the obstacles that may hinder the development of tourism object Walengkabola. The collecting data method of this research is observation and interview method, while analizing the data uses qualitative method. Research about strategy of developing tourism object Walengkabola with cultural based, is still waiting for the result of research and further analysis. The results show that the physical condition of tourism object Walengkabola is quite beautiful. Panorama and the views of beach are quite spectacular which has its own attraction and can be a tourism attraction. Some cultural attraction can be used as tourism packet, such as linda dance from Wuna tribe, horse fighting which is only found in Muna Regency, kite attraction, traditional self-defense arts, and mangaro which is the combination of dance and silat. Some obstacles have supported the development of tourism object Walengkabola, such as: lack of promotion, lack of awareness of local residents regarding the cleanliness of the marine environment, the lack of capital, the quality of damaged roads to tourism and the lack of available transportation modes to the tourist area. Keywords: tourism, culture, and development.